REFORM OF LIMITATION PERIOD INSTITUTE IN THE LEGISLATION OF THE RUSSIAN FEDERATION: ADVANTAGES AND MISTAKES (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
In article the limitation period institute innovations entered duringreforming of the civil legislation of the Russian Federation are analyzed.Advantages of new norms on definition of the beginning of limitationperiod are noted. The author gives an assessment of such innovation asthe objective limitation period and also analyzes the prospects of itsapplication to different types of the civil relations. Influence of theinternational acts in the field of private law on reforming of norms onlimitation period in Russia is reflected. The author touches also on issuesof influence of limitation period on the subjective substantive law whichis subject to protection.